Disparate roles of zinc in chemical hypoxia-induced neuronal death - Kim, Sujeong; Seo, Jung-Woo; Oh, Shin Bi; Kim, So Hee; Kim, Inki; Suh, Nayoung; Lee, Joo-Yong (Frontiers in Cellular Neuroscience, 2015)
Accumulating evidence has provided a causative role of zinc (Zn2+) in neuronal death following ischemic brain injury. Using a hypoxia model of primary cultured cortical neurons with hypoxia-inducing chemicals, cobalt chloride (1 mM CoCl2), deferoxamine (3 mM DFX), and sodium azide (2 mM NaN3), we evaluated whether Zn2+ is involved in hypoxic neuronal death. The hypoxic chemicals rapidly elicited intracellular Zn2+ release/accumulation in viable neurons. The immediate addition of the Zn2+ chelator, CaEDTA or N,N,N’N’-tetrakis-(2-pyridylmethyl) ethylenediamine (TPEN), prevented the intracellular Zn2+ load and CoCl2-induced neuronal death, but neither 3-hour-later Zn2+ chelation nor a non-Zn2+ chelator ZnEDTA (1 mM) demonstrated any effects. However, neither CaEDTA nor TPEN rescued neurons from cell death following DFX- or NaN3-induced hypoxia, whereas ZnEDTA rendered them resistant to the hypoxic injury. Instead, the immediate supplementation of Zn2+ rescued DFX- and NaN3-induced neuronal death. The iron supplementation also afforded neuroprotection against DFX-induced hypoxic injury. Thus, although intracellular Zn2+ release/accumulation is common during chemical hypoxia, Zn2+ might differently influence the subsequent fate of neurons; it appears to play a neurotoxic or neuroprotective role depending on the hypoxic chemical used. These results also suggest that different hypoxic chemicals may induce neuronal death via distinct mechanisms.